Mitochondria and Calcium Regulation as Basis of Neurodegeneration Associated With Aging - Müller, Marioly; Ahumada-Castro, Ulises; Sanhueza, Mario; Gonzalez-Billault, Christian; Court, Felipe A.; Cárdenas, César (Frontiers in Neuroscience, 2018)
Age is the main risk factor for the onset of neurodegenerative diseases. A decline of mitochondrial function has been observed in several age-dependent neurodegenerative diseases and may be a major contributing factor in their progression. Recent findings have shown that mitochondrial fitness is tightly regulated by Ca2+ signals, which are altered long before the onset of measurable histopathology hallmarks or cognitive deficits in several neurodegenerative diseases including Alzheimer’s disease (AD), the most frequent cause of dementia. The transfer of Ca2+ from the endoplasmic reticulum (ER) to the mitochondria, facilitated by the presence of mitochondria-associated membranes (MAMs), is essential for several physiological mitochondrial functions such as respiration. Ca2+ transfer to mitochondria must be finely regulated because excess Ca2+ will disturb oxidative phosphorylation (OXPHOS), thereby increasing the generation of ROS that leads to cellular damage observed in both aging and neurodegenerative diseases. In addition, excess Ca2+ and ROS trigger the opening of the mitochondrial transition pore mPTP, leading to loss of mitochondrial function and cell death. mPTP opening probably increases with age and its activity has been associated with several neurodegenerative diseases. As Ca2+ seems to be the initiator of the mitochondrial failure that contributes to the synaptic deficit observed during aging and neurodegeneration, in this review we aim to look at current evidence for mitochondrial dysfunction caused by Ca2+ miscommunication in neuronal models of neurodegenerative disorders related to aging, with special emphasis on AD.